Alcoholic hepatitis: appropriate indication for liver transplantation?. Issue 6 (December 2017) - Schneekloth, Terry D.; Niazi, Shehzad K.; Simonetto, Douglas A.
Abstract : Purpose of review: The majority of liver transplantation centers have required patients with alcohol-induced liver disease to demonstrate a period of abstinence (generally 6 months' duration) to qualify for transplant listing. This requirement has excluded patients with alcoholic hepatitis from transplant consideration. Since 2011, several studies have examined the outcomes of patients undergoing liver transplantation with brief abstinence as a lifesaving intervention for alcoholic hepatitis. This review includes each of the recent studies and discusses their implications for general transplant practice. Recent findings: A Medical Literature Analysis and Retrieval System search revealed five published studies – three prospective and two retrospective – pertaining to liver transplantation for alcoholic hepatitis. Among patients with medication-nonresponsive alcoholic hepatitis, those who underwent transplantation had superior survival. Liver recipients with alcoholic hepatitis had comparable survival to those with 6 or more months of abstinence. Their relapse rates were not statistically different in the short term over those transplanted with longer abstinence, although some patients in each prospective cohort relapsed to drinking despite narrow inclusion criteria and extensive pretransplant staff reviews and posttransplant surveillance. Summary: Liver transplantation is a reasonable treatment consideration for highly selective cases of alcoholic hepatitis. Further research is needed to refine inclusion criteria, address posttransplant relapse prevention interventions, and monitor long-term outcomes.